Soil zinc surveillance frameworks can inform human nutrition studies: opportunities in India - Khokhar, Jaswant S.; Broadley, Martin R.; Ander, E. Louise (Frontiers in Soil Science, 2024)
Mineral micronutrient deficiencies are widespread in global food systems and can affect plant growth, crop quality, and human and livestock health. The mapping of soils, and soil properties, linked to micronutrient supply in food systems is now enabling us to better understand the linkages between soil health and function and its relationship with food quality and human health. Zinc (Zn) deficiencies in Indian soils are of particular concern in the context of crop yields and food quality. This current review aims to understand the data landscapes on soil Zn and related soil properties in India.The scope of the review is to identify and describe data sets from national and statewide programmes, and research experiments, in which soil Zn has been reported, and which could be used to provide a framework for integrated surveys, which would combine wider agriculture, food systems, nutrition, and public health sectors. The largest data set on soil Zn was collected under a Soil Health Management (SHM) programme, during which the Indian government analysed more than 30 million soil samples for Zn concentration (mg kg -1 ) from 2015 to 2019. This study showed that 39% of Indian soils are considered Zn deficient for crop production (i.e. based on a threshold of <0.6 mg kg -1 ); soil Zn deficiency varied from 2 to 67% across different Indian states. In addition, the All India Coordinated Research Project on Micro and Secondary Nutrients and Pollutant Elements in Soils and Plants (AICRP-MSPE) programme analysed >240,000 soil samples from 2012 to 2018 and reported ~38% soil Zn deficiency in the Indian soils. There is no programme in India that currently maps micronutrients in soil and crops together using 'GeoNutrition' approaches recently reported in two countries in Africa, Ethiopia, and Malawi. Future co-ordinated Soil and crop micronutrient mapping in India can help us to understand better the movement of Zn (and other micronutrients) in food systems, and to inform strategies to improve the Zn status in the soil, e.g. use of Zn fertilisers for yield and agronomic biofortification, and in the edible tissues of crops, e.g. through genetic biofortification.